IMPLEMENTASI PERAN MANUSIA SEBAGAI PENGEMBANG ILMU DALAM KAJIAN FILSAFAT - Ela Irnanda Efendi; Sarda Nuria; Haidir; Yeni Erita; Yanti Fitria (STKIP Subang, 2023)
Humans have the cognitive capacity to engage in reasoning, and it is this cognitive capacity that forces human to advance their existing knowledge. The development of human potential is realized into the educational process because in education there is a process of developing knowledge and positioning human as full learning subjects. Philosophy of science and human life have a close relationship. The philosophy of science guides humans to carry out their lives wisely. This research uses a qualitative approach with the research method used is a literature review study that reviews previous finding related to the implications of the role of humans as developers of science in philosophical studies. The data analysis technique used is qualitative descriptive which aims to analyze the subject matter related to the relevant title.